Truth, growth, repeat : a business manual for generation why - Edmonds, Mike; Duncan, Ronnie (Wiley & Sons Australia, 2018)
The plain English guide to growing your business with purpose. Avoiding corporate jargon and overly-academic theorising in favor of a commonsense analysis of modern business behaviour, Truth, Growth, Repeat is like a user manual for company growth in a new world of commercial transparency. By mapping the way business works today at a very honest and human level, this street-smart book is a must-read for any business owner who wants to achieve growth and success without compromising their personal values. The book introduces The Circle of True Purpose, a virtuous sequence of knock-on effects that proves that enduring commercial growth is the result when a business owner's authentic motive is placed at the core of everything the business does. Author and brand expert Mike Edmonds explains the correct sequence to follow to acquire both financial return and personal fulfilment, and why going the other way leads to a never-ending cycle of inconsistent sales and consumer distrust. To illustrate these two key paths in life, the book contains many stories of actual businesses who've experienced these effects. This practical guide takes business owners through a series of exercises to help surface their own True Purpose and implement it in their sector of industry.-Get tips on growing your business authentically from an expert in translating complex theory into usable advice -Find out why truth is not only an admirable moral quality but is increasingly the key to lasting business success -Discover ways to surface your True Purpose and learn the actual steps you can take to implement them in our always-on, super-connected world -Bust the corporate myths that might be holding you back and obtain simple, usable tools that will help your higher ideal deliver higher returns If you feel there's a powerful truth inside your business that the world isn't seeing, Truth, Growth, Repeat could be the most important book you ever read.